Employee Referral, Social Proximity and Worker Discipline: Theory and Evidence from India - Amrita Dhillon; Vegard Iversen; Gaute Torsvik (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study an important mechanism underlying employee referrals into informal low skilled jobs in developing countries. Employers can exploit social preferences between employee referees and potential workers to improve discipline. The profitability of using referrals increases with referee stakes in the firm, and, in most cases, with the strength of the social tie between the referee and the new recruit. We provide an empirical counterpart to these results using primary data covering low- and unskilled migrants in India. Consistent with the theoretical predictions, we find a high prevalence of workplace referral and strong kinship ties between referees and new recruits. Finally, workplace intermediaries are different from and typically in more prestigious' jobs than those recruited.
Keywords: J41; J31; D82; D86; O12; O17; 330; networks; low- and unskilled jobs; India; moral hazard; employee referrals; efficiency wages; referee incentives; strength of ties